Whole-Body Roll Tilt Influences Goal-Directed Upper Limb Movements through the Perceptual Tilt of Egocentric Reference Frame - Tani, Keisuke; Shiraki, Yoshihide; Yamamoto, Shinji; Kodaka, Yasushi; Kushiro, Keisuke (Frontiers in Psychology, 2018)
In our day to day life, we can accurately reach for an object in our gravitational environment without any effort. This can be achieved even when the body is tilted relative to gravity. This is accomplished by the central nervous system (CNS) compensation for gravitational forces and torque acting on the upper limbs, based on the magnitude of body tilt. The present study investigated how performance of upper limb movements was influenced by the alteration of body orientation relative to gravity. We observed the spatial trajectory of the index finger while the upper limb reached towards a memorized target with the body tilted in roll plane. Results showed that the terminal location of the fingertip shifted towards the direction of body tilt away from the actual target location. The subsequent experiment examined if the perceived direction of the body longitudinal axis shifted relative to the true direction in roll plane. The results showed the perceived direction of the body longitudinal axis shifted towards the direction of the body tilt, which correlated with the shift of the terminal location in the first experiment. These results suggest that the dissociation between the egocentric and gravitational coordinates induced by whole-body tilt leads to systematic shifts of the egocentric reference frame for action, which in turn, influences the motor performance of goal-directed upper limb movements.